2000
DOI: 10.1107/s0108270199015024
|View full text |Cite
|
Sign up to set email alerts
|

Protonation products of pentaaminopentane as novel building blocks for hydrogen-bonded networks

Abstract: The structures of 3-amino-1,2R,4S,5-tetraammoniopentane tetrachloride monohydrate, C 5 H 21 N 5 4+ Á4Cl À ÁH 2 O, and 1,2R,3,4S,5-pentaammoniopentane tetrachlorozincate trichloride monohydrate, (C 5 H 22 N 5 )[ZnCl 4 ]Cl 3 ÁH 2 O, have been determined from single-crystal X-ray diffraction data. Both compounds show a complex network of NÐHÁ Á ÁO, OÐ HÁ Á ÁCl and NÐHÁ Á ÁCl hydrogen bonds. There are a total of 14 H atoms of the tetra-cation and 15 H atoms of the pentacation available for hydrogen bonding. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…A conformation with equatorial nitrogen donors was proposed for the doubly protonated species, and the low basicity was attributed to a particularly favorable intramolecular hydrogen bonding between the axial amino groups of the neutral triamine, that is destroyed upon protonation. This explanation appears, however, not to be fully conclusive, since it is generally assumed that hydrogen bonds between free amino groups are only weak. , The low basicity of 2,4,6-Me 3 tach also contradicts a report of Menger et al who found a high basicity for the isomeric 1,3,5-Me 3 tach . We therefore decided to repeat the p K a determination of 2,4,6-H 3 Me 3 tach 3+ and found indeed a significantly higher first protonation constant (Table a) than the one reported by Parker et al…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…A conformation with equatorial nitrogen donors was proposed for the doubly protonated species, and the low basicity was attributed to a particularly favorable intramolecular hydrogen bonding between the axial amino groups of the neutral triamine, that is destroyed upon protonation. This explanation appears, however, not to be fully conclusive, since it is generally assumed that hydrogen bonds between free amino groups are only weak. , The low basicity of 2,4,6-Me 3 tach also contradicts a report of Menger et al who found a high basicity for the isomeric 1,3,5-Me 3 tach . We therefore decided to repeat the p K a determination of 2,4,6-H 3 Me 3 tach 3+ and found indeed a significantly higher first protonation constant (Table a) than the one reported by Parker et al…”
Section: Resultsmentioning
confidence: 79%
“…This explanation appears, however, not to be fully conclusive, since it is generally assumed that hydrogen bonds between free amino groups are only weak. 16,37 The low basicity of 2,4,6-Me 3 tach also contradicts a report of Menger et al who found a high basicity for the isomeric 1,3,5-Me 3 tach. 14a We therefore decided to repeat the pK a determination of 2,4,6-H 3 Me 3 tach 3þ and found indeed a significantly higher first protonation constant (Table 3a) than the one reported by Parker et al…”
Section: Resultsmentioning
confidence: 90%
“…Their protonation products can serve as donors in hydrogen bonds and are therefore interesting building blocks for supramolecular structures [2], The metal complexing properties of 3-aminopyrrolidine have recently been described [3], however, a crystal structure determination of this ligand, its protonated form or its metal complexes has not been reported to the best of our knowledge. The structure of the title compound can be described in terms of layers, formed by cations of the same chirality together with one …”
Section: Discussionmentioning
confidence: 99%
“…[3] However, existing amino polymers, such as poly(ethylene imine) synthesized by cationic ring-opening polymerization [4] or poly(vinyl amine) prepared from vinylformamide [5] have just one amino group per two carbon atoms. Although low-molecular-mass compounds which are functionalized on each carbon atom are known from nature (carbohydrates), or from some examples in organic chemistry (for example, 1,2,3,4,5-penta-n-aminopentane), [6] to date an increased incorporation of "active" amino groups in polymers to improve the efficiency of additives for applications mentioned above has not been achieved.…”
mentioning
confidence: 99%